THE ROLE OF PPAT IN PROVIDING SOCIAL AND PUBLIC FACILITIES FOR SEPARATION OF LAND RIGHTS CERTIFICATES - Adistya Ayu Pratiwi FA; Ana Silviana (fakultas hukum universitas PGRI Semarang, 2023)
The obligation to hand over public facilities (fasum) and social facilities (fasos) by developers to local governments has been regulated through regulations from the central government. Beginning with the enactment of Law no.26 of 2007 on Spatial Planning, which was followed by Government Regulation (PP) No. 15 of 2010 concerning the Implementation of Spatial Planning, and in the City of Tangerang, PPAT has not involved PPAT in the formation of Regional Regulations for the City of Tangerang, thus causing new problems. This research uses descriptive socio-legal which is strengthened by prescriptive interpretation analysis, which is a method of finding law by interpreting/interpreting/prescriptive and writing based on secondary data and conducting interviews. The results of this study indicate that licensing in the administration of local government can be developed as one of the authorities of local governments whose implementation is reflected in the legal actions of regional heads, both on the basis of laws and regulations and in responding to the principles of good governance. The obligation to hand over public facilities (fasum) and social facilities (fasos) by developers to local governments has been regulated through regulations from the central government and in Tangerang City has not involved PPAT in the formation of Tangerang City Regional Regulations, so that in Tangerang the local regulations seem not to be implemented, causing various new problems